URGENSI INTERNALISASI NILAI KASIH SAYANG KEPADA IBU DALAM PENGUATAN KARAKTER ISLAMI ANAK PEREMPUAN: PERSPEKTIF PENDIDIKAN AGAMA ISLAM - Lili Epi Candra Yani; Uswatun Hasanah; Nur Azizah; Cossin Alfatex; Desti Umi Kalsum; Alihan Satra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the urgency of internalizing the value of love and compassion toward mothers in strengthening the Islamic character of girls from the perspective of Islamic Religious Education. Love and compassion toward mothers are part of the implementation of the values of birrul walidain (devotion to parents), which play a strategic role in shaping children’s morals, personality, and spirituality. This research employed a library research method by examining various relevant primary and secondary sources, including the Qur’an, hadith, books, and scientific articles related to character education and Islamic Religious Education. The data were analyzed using content analysis to identify concepts, values, and their relevance to character education. The findings indicate that the internalization of love and compassion toward mothers can foster attitudes of respect, empathy, responsibility, social awareness, and obedience to Allah SWT. These values serve as an essential foundation for developing the Islamic character of girls amid the challenges of modern society. Islamic Religious Education plays a central role in instilling and strengthening the value of love and compassion toward mothers through role modeling, habituation, and reinforcement of religious understanding. Therefore, the internalization of love and compassion toward mothers is a fundamental aspect of shaping a generation of Muslim women who possess strong Islamic character, noble morals, and a strong moral consciousness.